Optimization Model for an Airline Crew Rostering Problem: Case of Garuda Indonesia - Rieske Hadianti; Khusnul Novianingsih; Saladin Uttunggadewa; Kuntjoro A. Sidarto; Novriana Sumarti; Edy Soewono (Journal of Mathematical and Fundamental Sciences, 2013)
This paper discusses the cockpit crew rostering problem at Garuda Indonesia, taking into account a number of internal cockpit crew labor regulations. These internal labor regulations are in general more restrictive at Garuda Indonesia than at other airlines, so that modeling the cockpit crew rostering problem for Garuda Indonesia is challenging. We have derived mathematical expressions for the cockpit crew labor regulations and some technical matters. We model a non-linear integer programming for the rostering problem, using the average relative deviation of total flight time to the ideal flight time as the objective function. The optimization model have been tested for all classes of cockpit crews of Garuda Indonesia, using a simulated annealing method for solving the problem. We obtained satisfactory rosters for all crew members in a short amount of computing time. This shows that the optimization problem is well-defined.